PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DISERTAI MEDIA GAMBAR UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA DALAM PEMBELAJARAN BIOLOGI DI SMA NEGERI 3 SURAKARTA TAHUN AJARAN 2009/2010 - Widiastuti, Retno; Santosa, Slamet; Muzayyinah, Muzayyinah (Prosiding Seminar Biologi, 2010)
ABSTRACT Problem Based learning is kind of model in learning helps students to find problem from a real situation or science have the character of theoretical. Students will be more active in the learning process and able to develope their thinking and problem solving skills. The aim of this study was to improve XI-IA2 student?s self directed learn in Biology. The instrument used were observation sheets, enquette, and interview. The writer found an increase in student?s self directed learning. Kata-kata kunci: Problem Based Learning (PBL), media gambar, kemandirian belajar